Tendinopathy: injury, repair, and current exploration - Lipman K; Wang CC; Ting K; Soo C; Zheng Z (Dove Medical Press, 2018)
Kelsey Lipman,1 Chenchao Wang,2–4 Kang Ting,2 Chia Soo,4 Zhong Zheng2 1David Geffen School of Medicine, 2Division of Growth and Development, Section of Orthodontics, School of Dentistry, University of California, Los Angeles, CA, USA; 3First Hospital of China Medical University, Shenyang, China; 4Division of Plastic and Reconstructive Surgery, Department of Orthopaedic Surgery, Orthopaedic Hospital Research Center, University of California, Los Angeles, CA, USA Abstract: Both acute and chronic tendinopathy result in high morbidity, requiring management that is often lengthy and expensive. However, limited and conflicting scientific evidence surrounding current management options has presented a challenge when trying to identify the best treatment for tendinopathy. As a result of shortcomings of current treatments, response to available therapies is often poor, resulting in frustration in both patients and physicians. Due to a lack of understanding of basic tendon-cell biology, further scientific investigation is needed in the field for the development of biological solutions. Optimization of new delivery systems and therapies that spatially and temporally mimic normal tendon physiology hold promise for clinical application. This review focuses on the clinical importance of tendinopathy, the structure of healthy tendons, tendon injury, and healing, and a discussion of current approaches for treatment that highlight the need for the development of new nonsurgical interventions. Keywords: tendinopathy, tendon injury, tendon repair, healing